PENGARUH KEPEMIMPINAN TERHADAP KINERJA PEGAWAI NEGERI SIPIL PADA DINAS TENAGA KERJA DAN TRANSMIGRASI PROVINSI RIAU - mustika, aai (Sekolah Tinggi Ilmu Ekonomi Riau, 2019)
This study aims to examine and analyze the influence of leadership on the performance of government employees at the Department of Labor and transmigration Service in Riau Province. The variable in this study consisted of the dependent variable (performance) and the independent variable (leadership), the populations in this study as many 210 people. The samples in this study as many 67 people. Analysis of the data in this study using quatitative descriptive analysis ia a way to explain the result of existing research using mathematical formulas and equations linking theory, then deduced. Meanwhile, to test the feasibility of the data collected is used testing instrument validity, reliability, normality, determinaty coefficient, T test and simple linear regression test. The result of this study are simple linear regression Y=21.467+0,285X. Based on empirical data on the T test, an tcount > ttable is 2,468 > 1,668 an test result determinaty coefficient (R2) = 0,086 (8,60%) while the remaining is influenced bt other variables outside of this research. So H0 rejected and Ha accepted, meaning there is a significant influence between leadership and performance